Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/rlu.0000000000000537
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tumor Hypoxia in Head and Neck Cancer by PET With 62Cu-Diacetyl-Bis(N4-Methylthiosemicarbazone)

Abstract: Pretreatment ⁶²Cu-ATSM PET is useful for predicting the prognosis of patients with HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…19). This was supported by results from another recent study in which high pretreatment 62 Cu-ATSM tumor uptake correlated with a reduced PFS (20). However, it is not known to what extent Cu-ATSM reflects tumor hypoxia is questionable.…”
Section: Hypoxiasupporting
confidence: 55%
“…19). This was supported by results from another recent study in which high pretreatment 62 Cu-ATSM tumor uptake correlated with a reduced PFS (20). However, it is not known to what extent Cu-ATSM reflects tumor hypoxia is questionable.…”
Section: Hypoxiasupporting
confidence: 55%
“…Minagawa et al (2011) found that 62 Cu-ATSM SUV max , but not TMR, was significantly different in 17 locally advanced head and neck cancer patients with and without residual or recurrent tumours. A study of 25 head and neck cancer patients indicated that both increasing SUV max and TMR were associated with worse progression-free survival (Sato et al , 2014). Grassi et al (2014) used 64 Cu-ATSM to define a biological target volume in 11 patients with HNSCC and found this parameter, along with SUV max , to have high sensitivity but low specificity in predicting complete response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism has not been elucidated and uptake may be dependent on cell or tumour type, clinical studies have clearly demonstrated the potential as an imaging biomarker that warrants further investigation, especially in HNSCC, with clear advantages over the nitroimidazole-based hypoxia tracers (Minagawa et al , 2011; Grassi et al , 2014; Sato et al , 2014). …”
mentioning
confidence: 99%
“…Furthermore, clinical trials are also underway to assess the value of 18 F-HX4-PET in identifying microenvironment-associated treatment response in pancreatic (NCT01989000), head and neck (NCT01347281), and cervical cancers (NCT02233387). Lastly, uptake of the non-nimorazole PET marker Cu-ATSM has also been clinically correlated with therapeutic response in numerous tumor types, including lung [133,134], brain [135], and cervical cancers [134]. However, Cu-ATSM is not a direct marker of hypoxia and its mechanism is still largely unknown.…”
Section: Assessment Of Hypoxia and Treatment Responsementioning
confidence: 99%